WHAT'S NEXT IN THE CASEWORKER'S Digital Toolkit? Leveraging Advanced Technologies in Child Welfare. - Mills-Brinkley, Shelley; Cota, Roberto; Miller, Kathryn; McDonald, Jarria (Policy & Practice (19426828), 2017)
The article discusses the leverage of advanced technologies in the modern casework practice in child welfare. Information about the Comprehensive Child Welfare Information System (CCWIS) federal regulations in the U.S. that are considered a catalyst for infusing advanced technologies into child welfare casework is explored. The use of dark data analytics to provide the caseworker with insight to evaluate and take preventive measures is also outlined.